Financial Inclusion, Literacy, and SME Resilience: Emotional Well-Being Mediation - Hansen Hein Rumtutuly; Martha Racwel Patty (ARBITRASE: Journal of Economics and Accounting, 2026)
MSMEs play a vital role in Ambon City's economy but remain vulnerable to financial instability due to limited financial knowledge, restricted access to formal financial services, and increasing operational challenges. This study investigates the effects of financial literacy and financial inclusion on MSME financial resilience, with emotional well-being as a mediating variable. A quantitative explanatory approach was employed using survey data from 71 MSME owners selected through purposive sampling. The data were analyzed using SEM-PLS with SmartPLS software. The results show that financial literacy positively affects emotional well-being (? = 0.423, p < 0.001) and financial resilience (? = 0.336, p = 0.008). Financial inclusion also positively influences emotional well-being (? = 0.322, p = 0.006), although its direct effect on financial resilience is insignificant (? = ?0.214, p = 0.069). Emotional well-being has the strongest positive effect on financial resilience (? = 0.633, p < 0.001). The model explains 45.2% of the variance in emotional well-being and 57.6% of the variance in financial resilience, highlighting the importance of psychological factors in strengthening MSMEs’ capacity to cope with financial challenges. This study extends Financial Capability Theory by demonstrating that financial capability enhances financial resilience through emotional well-being as a key psychological mechanism. It also strengthens the theory’s empirical validity by providing evidence from MSMEs in the archipelagic region of Eastern Indonesia, where limited financial access, high logistics costs, and greater economic vulnerability shape a distinct business environment.